The effect of price and service quality on the interest in repurchasing: citylink airlines in indonesia - Didi Tarmidi; Irawan Wijaya (Institute of Computer Science (IOCS), 2023)
The development of business in the Indonesian air transportation sector is an opportunity and challenge for airlines to meet aviation needs. Citilink as one of the airlines that experiences problems related to meeting aircraft occupancy due to the competition map of airlines in Indonesia is quite numerous by offering various services to get customer satisfaction so that repurchases occur, Citilink's challenge in maintaining prices and service quality so that repurchase interest can continue to increase is important. The research method used in this study is a quantitative method with a descriptive type of research. Sampling was carried out using a non-probability sampling technique used was purposive sampling with a total of 400 respondents who were users of Citilink Indonesia airlines. Meanwhile, the data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results showed that the Price variable in the very good category was 85%, the Service Quality variable was already in the excellent category by 86%, and the repurchase interest variable in the very good category was 86%. Price and Service Quality had a positive and significant effect on repurchase interest with a large influence of 52.6% and the remaining 47.4% influenced by other factors that were not studied.